(untitled) (Iranian Journal of Kidney Diseases, 2013)
We report a 16-year-old previously healthy boy who was admitted to hospital with fever, constitutional symptoms, purpura, additive arthritis, dysentery, rapid progressive renal failure, resembling Henoch- Schuenlein purpura, accompanied with retropharyngeal abscess. Kidney biopsy revealed rapid progressive glomerulonephritis with crescent formation, without immune deposition in immune fluorescent study. Serologic study revealed positive proteinase antineutrophil cytoplasmic antibody (ANCA). Intravenous methyl prednisolone plus and cyclophosphamide pulse were administered with a diagnosis of ANCA-associated vasculitis. Serum creatinine level reduced during the treatment and the patients was discharged with good clinical condition. This was the first case in which the ANCA-associated vasculitis was presented with retropharyngeal abscess. Other unusual findings were bloody diarrhea, raised purpura, and additive arthritis in an adolescence, which are more characteristic for Henoch-Schuenlein purpura.